2022
DOI: 10.3390/epigenomes6010007
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Status of Exon IV of the Brain-Derived Neurotrophic Factor (BDNF)-Encoding Gene in Patients with Non-Diabetic Hyperglycaemia (NDH) before and after a Lifestyle Intervention

Abstract: BDNF signalling in hypothalamic neuronal circuits is thought to regulate mammalian food intake. In light of this, we investigated how a lifestyle intervention influenced serum levels and DNA methylation of BDNF gene in fat tissue and buffy coat of NDH individuals. In total, 20 participants underwent anthropometric measurements/fasting blood tests and adipose tissue biopsy pre-/post-lifestyle (6 months) intervention. DNA was extracted from adipose tissue and buffy coat, bisulphite converted, and pyrosequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The brain-derived neurotrophic factor (BDNF) supports the development, survival, and maintenance of neurons 1 . Modern research has shown that receptors of BDNF are present in the peripheral vasculature, where it promotes endothelial cell survival, angiogenesis, and vascular integrity [2][3][4] . Blood contains BDNF as well [5].…”
Section: Introductionmentioning
confidence: 99%
“…The brain-derived neurotrophic factor (BDNF) supports the development, survival, and maintenance of neurons 1 . Modern research has shown that receptors of BDNF are present in the peripheral vasculature, where it promotes endothelial cell survival, angiogenesis, and vascular integrity [2][3][4] . Blood contains BDNF as well [5].…”
Section: Introductionmentioning
confidence: 99%